Biological effect and molecular mechanism study of biomaterials based on proteomic research. Issue 7 (July 2017) - Zhen, Zhen; Zheng, Yufeng; Ge, Zigang; Lai, Chen; Xi, Tingfei
Abstract: Along with the role transformation of biomaterials from bioinert substitute to regenerative inducer, the biological effect and mechanism of material-organism interaction become more important. Since most of animal tests and cellular experiments stay on the phenomenon description instead of mechanism interpretation, the development of proteomics technologies provides a golden opportunity to uncover the molecular interaction mechanism between biomaterial-organism on whole scale. This review summarizes current application of proteomics in biological effect and mechanism study of biomaterials, and discusses the development and challenges for future studies.